Social media campaigns, electoral momentum, and vote shares: evidence from the 2016 Hong Kong Legislative Council election. Issue 6 (2nd November 2018) - Tang, Gary; Lee, Francis L. F.
ABSTRACT: By studying candidates' Facebook fan pages and rolling poll data during the Hong Kong Legislative Council election in 2016, this article aims at examining the relationships between candidates' campaign performance on social media, electoral momentum, and vote shares. We contend that, under specific contextual conditions, social media campaigns could affect candidates' momentum during the election period, which can in turn affect vote shares. We also examine how the relationships between social media performance and electoral momentum vary according to the candidates' background characteristics, including age, political affiliation, incumbency status, and scale of the campaign of the political group to which the candidates belong. The results show that candidates' social media performance can indeed predict vote shares indirectly via the mediation of electoral momentum. The predictive power of social media performance is stronger for pro-democracy candidates, incumbents, and candidates belonging to political groups with larger election campaigns.